Electric field assisted reduction of NOx emission: A numerical study - Ahmed, Sheikh F.; Aghdam, Ali Charchi; Pleis, Jackson; Geiger, Robert; Farouk, Tanvir I. (Frontiers in Thermal Engineering, 2023)
The paper reports simulation results on the influence of a DC driven radial electric field on the emission characteristics; especially NOx and CO of a premixed methane/air laminar jet flame. A multi-physics computational model is developed in the OpenFOAM framework to simulate electric- field-coupled premixed combustion process. The computational framework consists of coupled species, momentum and energy conservation together with a Poisson’s equation solver to resolve the electric field distribution. Electron and ion conservation equations are resolved to consider the ionic wind body force in the momentum conservation equation and the associated possible electric field distortion due to the space charge distribution. The simulations are conducted for a stochiometric and fuel rich condition and over a range of jet flow rates for a configuration representative of a test-scale experimental setup. The model predictions show that for an applied voltage of 50 kV, the flame structure changes significantly for both the stoichiometric and fuel rich conditions. The flame is stretched significantly by the electric field due to ionic wind. For the fuel rich condition, the ionic wind allows additional mixing of the fuel rich stream with the surrounding air and drastically altering the flame structure. The electric field was found to reduce the NOx emission significantly for both stoichiometric and rich conditions. Over the entire range of flowrate conditions, the stochiometric fuel-oxidizer mixture showed a decrease in maximum NOx by a factor of 1.6 in presence of electric field. For the fuel rich case, however as the flow rate is increased, the NOx reduction factor decreased from 12.0 to 1.6. For CO emissions, the presence of electric field reduces the concentration under fuel rich conditions and vice versa for the stoichiometric flame. The role of kinetics is analyzed and discussed. Predicted NOx and CO emissions reductions due to electric field are compared with experimental measurements and the trends are found to agree favorably.